Changes of Longissimus Muscle Area and Rump Fat Thickness in Hungarian Simmental Fattening Bulls Measured Using Real-Time Ultrasound Equipment - Tőzsér, János; Holló, Gabriella; Holló, István; Seregi, János; Szentléleki, Andrea; Repa, Imre; Zarándoki, Rita; Minorics, Richárd (Acta Agraria Debreceniensis, 2005)
The aim of the authors was to evaluate changes in the longissimus muscle area (LMA) and rump fat thickness (P8) based on real-time ultrasound scanning in the Hungarian Simmental cattle breed. Ultrasonic measurements were carried out on the same 11 Hungarian Simmental fattening bulls by Falco 100 (Pie Medical) equipment (I.: age: 357±23.47 days, live weight: 475.55±51.40 kg; II.: age: 418±23.47 days, live weight: 555.10±54.11 kg) on two occasions. Animals were kept in small groups, on deep litter, and fed on silage and concentrate. LMA and P8 were measured on the scans, between the 12th and 13th ribs by manual outlining. Results for the investigated traits during the examinations were as follows: P8: I.: 0.373±0.154 cm, II.: 0.624±0.161 cm; LMA: I.: 65.72±5.89 cm2, II.: 71.74±8.94 cm2. During the fattening period, P8 increased significantly (I-II.: t=3.73, P